Manderley : POEMS - Wolff, Rebecca, 1967- (Book collections on Project MUSE., 2001)
Selected by Robert Pinsky as one of five volumes published in 2001 in the National Poetry Series_x000B__x000B__x000B__x000B_In the Manderley of Rebecca, Daphne du Maurier's forbidding haven of mocking ghosts and secrets that refuse to remain buried, nothing is as it seems. So in this stunning debut collection by Rebecca Wolff, cities, partners, mothers, sisters, friends, and perfect strangers all disguise their true faces, while they who seek connection are "transported from one great gaping / hole in the fabric / of our knowledge to another." _x000B__x000B__x000B__x000B_No passage is too dark, no garden too tangled for the troubled dreamer of Manderley. Wolff turns a quicksilver gaze on a fluid world where both the real and the imaginary are transfigured. Tempering steely candor with a sophisticated delight in wordplay, these poems turn on a dime from the sensual to the eerie, the resigned to the hopeful, the comforting to the shocking. Each poem weaves together layers of dream, remembrance, and fantasy, distilling from romantic excess a gritty, spare language of truth-telling and surprise._x000B__x000B_